What the Tortoise Says about Statutory Interpretation: The Semantic Canons of Construction Do Not Tip the Balance. (9th April 2022) - Afrouzi, Amin Ebrahimi
Abstract: Karl Llewellyn's critique of the canons of statutory interpretation led to a decline in their use for several decades. His critique, however, faced sustained resistance from some corners of the academy and the judiciary. Although this resistance has had only a selective uptake, it animated a gradual revival of the canons and brought the state of scholarship to an impasse that is for the most part partisan. In this article, I examine the semantic canons from a deeper level and argue that a universal assumption about them is false. Said assumption is that, although not dispositive, the semantic canons at least offer some reasons in favour of or against a candidate interpretation. Inclinations to rely on the semantic canons are also based on this assumption, although it is an assumption that the critics of the canons also share. I argue that this assumption is false because the semantic canons are a class of rules that are by nature not reason-giving. This provides a new ground against giving the semantic canons deliberative weight in questions of statutory interpretation.